Proceedings of the 16th Conference on Computational Linguistics - 1996
DOI: 10.3115/993268.993309
|View full text |Cite
|
Sign up to set email alerts
|

Anaphora resolution of Japanese zero pronouns with deictic reference

Abstract: This paper proposes a method to resolve the reference of deictic Japanese zero pronouns which can be implemented in a practical machine translation system. This method focuses on semantic and pragmatic constraints such as semantic constraints on cases, modal expressions, verbal semantic attributes and conjunctions to determine the deictic reference of Japanese zero pronouns. This method is highly effective because the volume of knowledge that must be prepared beforehand is not very large and its precision of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 4 publications
2
19
0
Order By: Relevance
“…In AR, the research trend has been shifting from rule-based approaches [Baldwin 1995;Lappin and Leass 1994;Mitkov 1997] to empirical, or corpus-based, approaches [McCarthy and Lehnert 1995;Ge et al 1998;Soon et al 2001;Ng and Cardie 2002;Strube and Müller 2003;Yang et al 2003;Ng 2004;Yang et al 2005] because the latter are shown to be a cost-efficient solution achieving a performance that is comparable to best-performing rule-based systems (see the Coreference task in Message Understanding Conference (MUC) 1 and the Entity Detection and Tracking task in the Automatic Content Extraction (ACE) program 2 ). The same trend is observed also in Japanese zero-anaphora resolution, where the findings made in rule-based or theory-oriented work [Kameyama 1986;Walker et al 1994;Nakaiwa and Shirai 1996;Okumura and Tamura 1996;Murata and Nagao 1997] have been successfully incorporated in machine-learning-based frameworks [Seki et al 2002;Iida et al 2003;Isozaki and Hirao 2003]. …”
Section: Introductionsupporting
confidence: 70%
“…In AR, the research trend has been shifting from rule-based approaches [Baldwin 1995;Lappin and Leass 1994;Mitkov 1997] to empirical, or corpus-based, approaches [McCarthy and Lehnert 1995;Ge et al 1998;Soon et al 2001;Ng and Cardie 2002;Strube and Müller 2003;Yang et al 2003;Ng 2004;Yang et al 2005] because the latter are shown to be a cost-efficient solution achieving a performance that is comparable to best-performing rule-based systems (see the Coreference task in Message Understanding Conference (MUC) 1 and the Entity Detection and Tracking task in the Automatic Content Extraction (ACE) program 2 ). The same trend is observed also in Japanese zero-anaphora resolution, where the findings made in rule-based or theory-oriented work [Kameyama 1986;Walker et al 1994;Nakaiwa and Shirai 1996;Okumura and Tamura 1996;Murata and Nagao 1997] have been successfully incorporated in machine-learning-based frameworks [Seki et al 2002;Iida et al 2003;Isozaki and Hirao 2003]. …”
Section: Introductionsupporting
confidence: 70%
“…Traditional approaches to zero anaphora resolution are based on manually created heuristic rules (Kameyama, 1986;Walker et al, 1994;Okumura and Tamura, 1996;Nakaiwa and Shirai, 1996), which are mainly motivated by the rules and preferences introduced in Centering Theory (Grosz et al, 1995). However, the research trend of zero anaphora resolution has shifted from such rule-based approaches to machine learningbased approaches because in machine learning we can easily integrate many different types of information, such as morpho-syntactic, semantic and discourse-related information.…”
Section: Related Workmentioning
confidence: 99%
“…There have been several efforts to computationally deal with this challenge. See LeNagard & Koehn (2010) and Nakaiwa & Shirai (1996). Identification is not the problem, when they read.…”
Section: Findings and Discussionmentioning
confidence: 99%